NILAI MORAL ORANG JAWA PEDESAAN: KAJIAN SEMIOTIKA NOVEL NGLEBUR WIRANG - Sinatrya Farhan Pramudito; Sucipto Hadi Purnomo (Universitas Muhammadiyah Surabaya, 2025)
Moral degradation in various parts of the country is a concern for various groups today, especially in an era that is fast-paced and full of change. Novels as literary works that reflect social life often display all aspects of life, including moral values. Similarly, the Javanese novel, in addition to narrating the life of the Javanese, also elaborates on the aspect of morality of this largest ethnic in Indonesia. Therefore, the purpose of this study is to describe the moral values of rural Javanese in the novel Nglebur Wirang by Yosep Bambang Margono. This study uses a qualitative approach. The data analysis technique uses Charles Sanders Peirce's semiotics. The research data is in the form of speech, attitudes, and actions that show the moral values of rural Javanese. The data collection technique used is to watch and record. The results of the study show that the novel Nglebur Wirang by Yosep Bambang Margono contains various moral values of rural Javanese. These values are such as tepa slira, hormat, nrima, pakewuh, sowan, sabar, isin, rasan-rasan, drengki, gumunan, nastiti, and blaka suta. Based on the results of the research, the moral values of rural Javanese people provide a deep understanding of the value systems that shape the behavior and perspective of traditional communities. These values are not only believed philosophically, but also manifested in daily life.